Diskursus Pembagian Warisan Bagi Perempuan: Kritik Penafsiran Surah An-Nisa’ Ayat 11 Dan 176: A CRITIQUE OF THE INTERPRETATION OF SURAH AL-NISĀ' VERSES 11 AND 176 - Asfa Kurnia Rachim; Nurul Afifah (Department Islamic Education, Faculty of Education and Teacher Traning, Universitas Islam Bandung, 2024)
The legal issue of the distribution of inheritance for women with a ratio of 2: 1 which is stated in the Qur'an Surah Al-Nisā' verses 11 and 176 reaps many pros and cons in its interpretation. This is evidenced by many writings and books written by Muslim scholars to express criticism of interpretation and perspective in examining the law contained in the inheritance verse. The phrase equality and justice led to the issue of equal distribution of inheritance between men and women. This was pioneered by feminists. Through this, it appears that the distribution of inheritance for women needs to be studied further. The focus of the study of this paper is how to criticize the interpretation of the mufasir scholars on the inheritance verse of surah Al-Nisā' verses 11 and 176. By using a qualitative approach and library research method, this study shows that the law of inheritance distribution received by women has received a lot of criticism both pro and con from the scholars of interpretation. This study shows that those who are in favor of the distribution of women's inheritance with a ratio of 2: 1, namely Muhammad Abduh, Tabatabai, and Muhammad Syahrur with their maximum limit theory. Those who are against and have new ideas are Amina Wadud and Munawir Sjadzali.